2011
DOI: 10.1111/j.1365-2923.2011.03988.x
|View full text |Cite
|
Sign up to set email alerts
|

Applying multimedia design principles enhances learning in medical education

Abstract: Multimedia design principles are easy to implement and result in improved short-term retention among medical students, but empirical research is still needed to determine how these principles affect transfer of learning. Further research on applying the principles of multimedia design to medical education is needed to verify the impact it has on the long-term learning of medical students, as well as its impact on other forms of multimedia instructional programmes used in the education of medical students.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
147
0
8

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(164 citation statements)
references
References 18 publications
4
147
0
8
Order By: Relevance
“…editing the current lecture slides to ensure they are all relevant to the matter in hand and that the context of the session is clear and explicit (being careful to try and adopt the point of view of the learner); 2. where necessary, re-designing slides to cognitively support the learner, using current, evidence-based approaches (Mayer and Moreno, 2003;Issa et al, 2011); 3. developing support materials for students to use either before or after the face-to-face session to complement their own learning strategy; 4. embedding a catch-up segment at the beginning of each lecture to ensure everyone in the class has the background knowledge needed to engage meaningfully; 5. utilizing suitable technology to continually facilitate engagement, interaction, and questioning during the session.…”
Section: Solution: the Active Lecturementioning
confidence: 99%
“…editing the current lecture slides to ensure they are all relevant to the matter in hand and that the context of the session is clear and explicit (being careful to try and adopt the point of view of the learner); 2. where necessary, re-designing slides to cognitively support the learner, using current, evidence-based approaches (Mayer and Moreno, 2003;Issa et al, 2011); 3. developing support materials for students to use either before or after the face-to-face session to complement their own learning strategy; 4. embedding a catch-up segment at the beginning of each lecture to ensure everyone in the class has the background knowledge needed to engage meaningfully; 5. utilizing suitable technology to continually facilitate engagement, interaction, and questioning during the session.…”
Section: Solution: the Active Lecturementioning
confidence: 99%
“…Rummer, Schweppe, Furstenberg & Scheiter (2011) observed the modality effect in comparing the simultaneous presentation of texts and pictures. Similarly, Kalyuga, Chandler & Sweller (2000) as well as Issa, Schuller, Santacaterina, Shapiro, Wang, Mayer & DaRosa (2011) found statistically significant improvements in retention and total posttest scores for students instructed using principles of multimedia design compared with those instructed using the traditional design. And, most recently, Bull (2013) concluded that when designing digital interactive learning materials instructors should ensure that information is presented in at least two modes (text, video, picture, animation and audio) of representation for clarity and understanding; since using at least two modes of representation creates a multimedia learning effect, which enables learners to effectively develop verbal and visual models and build functional connections between them.…”
Section: Does Modality Effect Cognition?mentioning
confidence: 99%
“…An established approach to measuring learner gain from TEL resources already exists in the form of pre-and post-testing (Issa et al 2011). Not only does this allow a direct measure of learner gain to be ascertained, it provides information on the duration of time for which knowledge has been retained.…”
Section: Measuring: Degree Of Equity In Learner Gain Between Developementioning
confidence: 99%
“…It is anticipated however, that at this stage, and irrespective of resource type, an increase in learner gain would have been achieved. It is essential, therefore, to perform a subsequent series of post-tests to ascertain the degree of knowledge retention between the two resource types over time (Hake 1998;Issa et al 2011). …”
Section: Measuring: Degree Of Equity In Learner Gain Between Developementioning
confidence: 99%